DO FAMILY OWNERSHIP AND GROWTH OPPORTUNITY AFFECT FIRM VALUE? - Nurul Sulistiyani; Khomsiyah Khomsiyah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study investigates the effect of family ownership and growth opportunity on firm value, with female directors serving as a moderating variable. The research is motivated by the increasing dominance of family-controlled firms in emerging markets and the growing attention to gender diversity in corporate governance. The sample consists of consumer non-cyclical companies listed on the Indonesia Stock Exchange (IDX) over the period 2022–2024. Data are analyzed using Moderated Regression Analysis (MRA) to examine both direct and moderating relationships among the variables. The results indicate that family ownership has a positive influence on firm value, suggesting that concentrated ownership may enhance monitoring effectiveness and long-term strategic orientation. Growth opportunity is also found to positively affect firm value, reflecting the market’s favorable response to firms with strong future growth prospects. Furthermore, the presence of female directors strengthens the relationship between family ownership and firm value, as well as between growth opportunity and firm value. This finding highlights the role of female directors in improving board effectiveness, decision-making quality, and governance transparency. Overall, this study provides empirical evidence that gender diversity on corporate boards contributes to higher firm value, particularly in family-owned firms. The findings imply that integrating female directors into board structures can enhance the positive impact of ownership structure and growth potential on firm performance, offering valuable insights for investors, policymakers, and corporate managers in Indonesia.